Job Design and Employee Engagementof the National Institute of GreaseENAP) - Ben houiaa, ZEHOR; Yaaqoub , Mohamed (Milev Journal of Research and Studies, 2022)
Background: There are many variables that affect the organizational commitment of human resources . One of these variables is jobs design because it is related to tasks, duties and responsibilities that are carried out by individuals Objectives: this study aims at determining the relationship between jobs design and its dimensions of the organizational commitment of human resources, in «the National Foundation of paint making in « Sig state of mascara ». sample and the methods: there are 172 permanent employees in the Foundation they were selected through a stratified random sample that amounted or reached 63 employees ; The Data were collected using a questionnaire and interview tool in accordance with the "job design model (Frederick P. Morgeso, Stephen E. Humphrey,2006 ) and organizational commitment model (Meyer and Allen, 1997), The data of study were analysed according to correlation analysis and multiple regression analysis according to the method of Entrée. Results: There was significant statistical correlation between the jobs design and organizational commitment, ( pearson = 0,639 ** / sig=0.000) ;Also , there is a significance effect of job Context (β =0,333) on the organizational commitment.